Fabrication of High-Uniformity and High-Reliability Si3N4/AlGaN/GaN MIS-HEMTs With Self-Terminating Dielectric Etching Process in a 150-mm Si Foundry - Hui Sun; Wang, Maojun; Jianguo Chen; Liu, Peng; Kuang, Wenteng; Meihua Liu; Hao, Yilong; Dongmin Chen (IEEE TRANSACTIONS ON ELECTRON DEVICES, 2018)
A novel early gate dielectric AIGaN/GaN metal-insulator-semiconductor high-electron-mobility transistors (MIS-HEMTs) process is reported. With the highquality Si3N4 dielectric by low-pressure chemical vapor deposition and damage free, self-terminating passivation layer etching at the gate area, the MIS-HEMTs on 150-mm Si substrate demonstrate excellent output performance and good uniformity. The interface trap density between the gate insulator and the barrier layer is as low as 2 x 10(12) cm(-2).eV(-1) extracted by the conductance method. The MIS-HEMT fabricated on the wafer delivers an extremely small gate leakage current of 10(-9) mA/mm and a high I-on/I-off ratio of 10(11). The subthreshold swing (SS) is around 80 mV/dec, and the saturated output current density is 750 mA/mm. The dynamic on-resistance increases about 42% at a quiescent drain bias of 600 V. The V-th shift is -0.63 and -0.89 V at a high temperature of 200 degrees C and negative gate-bias stress of -25 V, respectively, indicating a comparable stability with the state-of-the-art MIS-HEMTs. An excellent threshold voltage and SS uniformity (1 - sigma/mu) with the value of 94.5% and 95.2% are achieved on the 150-mm wafer.
Keywords: AlGaN/GaN; damage-free etching; early dielectric; metal-insulator-semiconductor high-electron-mobility transistors (MIS-HEMTs); self-terminating; Si compatibility; uniformity